Endothelial-Specific Deficiency of ATG5 (Autophagy Protein 5) Attenuates Ischemia-Related Angiogenesis. Issue 6 (June 2019) - Sprott, David; Poitz, David M.; Korovina, Irina; Ziogas, Athanasios; Phieler, Julia; Chatzigeorgiou, Antonios; Mitroulis, Ioannis; Deussen, Andreas; Chavakis, Triantafyllos; Klotzsche-von Ameln, Anne
Abstract : Objective—: Pathological angiogenesis, such as exuberant retinal neovascularization during proliferative retinopathies, involves endothelial responses to ischemia/hypoxia and oxidative stress. Autophagy is a clearance system enabling bulk degradation of intracellular components and is implicated in cellular adaptation to stressful conditions. Here, we addressed the role of the ATG5 (autophagy-related protein 5) in endothelial cells in the context of pathological ischemia-related neovascularization in the murine model of retinopathy of prematurity. Approach and Results—: Autophagic vesicles accumulated in neovascular tufts of the retina of retinopathy of prematurity mice. Endothelium-specific Atg5 deletion reduced pathological neovascularization in the retinopathy of prematurity model. In contrast, no alterations in physiological retina vascularization were observed in endothelial-specific ATG5 deficiency, suggesting a specific role of endothelial ATG5 in pathological hypoxia/reoxygenation–related angiogenesis. Consistently, in an aortic ring angiogenesis assay, endothelial ATG5 deficiency resulted in impaired angiogenesis under hypoxia/reoxygenation conditions. As compared to ATG5-sufficient endothelial cells, ATG5-deficient cells displayed impaired mitochondrial respiratory activity, diminished production of mitochondrial reactive oxygen species and decreased phosphorylation of the VEGFR2 (vascular endothelial growth factor receptor 2). Consistently, ATG5-deficient endothelial cells displayed decreased oxidative inactivation of PTPs (phospho-tyrosine phosphatases), likely due to the reduced reactive oxygen species levels resulting from ATG5 deficiency. Conclusions—: Our data suggest that endothelial ATG5 supports mitochondrial function and proangiogenic signaling in endothelial cells in the context of pathological hypoxia/reoxygenation–related neovascularization. Endothelial ATG5, therefore, represents a potential target for the treatment of pathological neovascularization-associated diseases, such as retinopathies. Abstract : Supplemental Digital Content is available in the text.